Klimawandel im Supermarkt (Climate change in the supermarket) - Reufels, Bernd; Engels, Ioanna (2016)
German TV documentary that shows CC impacts on popular food stuff. Included a large segment on coffee in Colombia with CCAFS researcher Christian Bunn being interviewed and involved in the production. 1.3mio views on its main airing, 5 or more repeats on smaller channels and channel web site. Excerpts were used in different shows (morning show etc) and evening news.